A study of female sexual dysfunction by using female sexual functional index (FSFI) among women at the age of 40-55 years old in Universiti Sains Malaysia, Kubang Kerian, Kelantan - Karimah, Mohd (2008)
Sexual life is considered crucial issues in determining the well being of women through out their life. This is the important aspect of quality of life, reflects on physical, psychological and mental well being of the individual. Middle age women are additionally influenced by the hormonal changes surrounding menopause that affects their sexual function especially libido and orgasm. The aim of this study is to determine the prevalence of sexual dysfunction among women at the age of 40-55 years old. To determine which socio-demographic and sexual domain that influence libido or desire and orgasm domain, and the impact on HR T on sexual domain. A cross-sectional descriptive analysis was conducted on 434 local women at the age of 40-55 years old attending HUSM. Sexual function was measured by using selfadministered validated questionnaire Malay version which was Female Sexual Functional Index (FSFI). The questionnaire consist of socio-demographic data, and 19-item, multidimensional self report measure of female sexual functioning. It covers 6 basic domains of female sexual functions: desire, arousal, lubrication, orgasm, satisfaction, and pain. The analysis was performed by using X2 test and multivariate regression analysis. The mean age of the women was 47.5 (SD 4.33) years old. The overall prevalence of sexual dysfunction was 8.0%. The prevalence of sexual dysfunction for each domain was 18.4% for desire, 5.1% arousal, 4.4% lubrication, 6.9% pain, 2.1% orgasm, 7.4% satisfaction. The most significant predictor for desire were aged 40-45 and aged >50-55 (p-value=0.047, 0.017), Malays (p-value=0.024), Chinese (p-value=0.013), sexual arousal (P<O.OO 1 ), lubrication (P<O.OO 1 )and satisfaction domain(P<O.OO I). Lubrication and medical illness (renal disease) had a significant association with the lack of orgasm. (p<0.05). Aging, parity 2-5 and >5 and lack of lubrication significantly associated with sexual pain disorders (P<0.05). Hormone replacement therapy (HRT) did not significantly improved any sexual domain. Other socio-demographic variables such as level of education, type of occupation, duration of marriage and medical illness were less likely to result in disturbances on sexual function. The prevalence of sexual dysfunction among local women at the age of 40-55 years old was not high. The most affected sexual function domain was desire. There is a negative association between age and sexual response in middle age women and from this study we found that HRT did not have any impact on the sexual domain.